RETRACTION Yani, A., Henjilito, R., Noviardila, I., Hasan, B., Setyawan, H., Shidiq, A. A. P., Gerdijan, N., Latino, F., Eken, Özgür, Zulbahri, Z., Kurniawan, A. W., & HB, G. (2024). El papel de los supervisores escolares en la garantía de calidad del aprendizaje de la educación física: Una revisión sistemática (The Role of School Supervisors in the Quality Assurance of Physical Education Learning: A Systematic Review). Retos, 57, 589–597. https://doi.org/10.47197/retos.v57.107189 - RETOS, RETOS (Retos, 2025)
Yani, A., Henjilito, R., Noviardila, I., Hasan, B., Setyawan, H., Shidiq, A. A. P., Gerdijan, N., Latino, F., Eken, Özgür, Zulbahri, Z., Kurniawan, A. W., & HB, G. (2024). El papel de los supervisores escolares en la garantía de calidad del aprendizaje de la educación física: Una revisión sistemática (The Role of School Supervisors in the Quality Assurance of Physical Education Learning: A Systematic Review). Retos, 57, 589–597. https://doi.org/10.47197/retos.v57.107189Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI.Autores en el Word del artículo enviado a revisión: 10Autores en el PDF publicado con los autores modificados: 12Diferencia de los autores entre ambos momentos: +8 y -6 (Añadidos: Ahmad Yani, Raffly Henjilito, Iska Noviardila, Baharuddin Hasan, Nikolina Gerdijan, Zulbahri, Ari Wibowo Kurniawan, Gusliana HB. Eliminados: Roziah Roziah, Nuridin Widya Pranoto, Arief Darmawan, Muhammad Imam Rahmatullah, Ratko Pavlovic, Francesco Tafuri)